Race and Incest in Mann's "Blood of the Walsungs" - Gloria Chasson Erlich (Studies in 20th & 21st Century Literature, 1978)
No German or English edition of "The Bloood of the Walsungs" concludes with the sentence that Mann wrote for the original version in 1905, a sentence that begins and ends with two Yiddish words that conclusively identify the Aarenhold family as Jewish. The story, suppressed until 1921, draws heavily on the family of his new wife, Katya Pringsheim, a twin of Jewish extraction. Mann juxtaposes the incest of a pair of German-Jewish twins, Siegmund and Sieglinde Aarenhold, with the myth of the Walsungs, subtly manipulating the Wagner libretto to make it express his sense of the condition of the assimilated German Jew. The incest becomes a metaphor for Jewish exclusiveness as well as a type of the great sin which in many of Mann's works is regarded as a prerequisite to creativity. Like the Joseph series, "Blood of the Walsungs" portrays the paradoxical position of the Jew as resident alien.
Keywords: Thomas Mann; Blood of the Walsungs; incest; Jewish; Jews; Wagner